THE MANAGEMENT OF KNOWLEDGE AND THE EXPERTISES DEVELOPED IN HIGHER EDUCATION - Arielly Kizzy Cunha; José Anderson Santos Cruz; José Luís Bizelli (Revista on line de Política e Gestão Educacional)
The article deepens Reflections on knowledge management in front of technological innovations, describing aspects of the current society in the quest for acquiring and structuring skills to meet a constantly changing labour market. In an increasingly enterprising labor universe, continuous improvement of the workforce to incorporate innovative technologies is a requirement that can make a difference for ingress and permanence in complex organizations. Top-level professionals trainees must graduate to meet a society that demands leaderships with social commitment and solid formation for solving technological challenges through ethical and politically correct procedures. Some expertises demand lifelong development, from basic training to the steps that follow the graduation, and are related to the construction of humanized relationships in work through the interaction between professional fields, in which workers are led to reflect on their actions in the social, political, economic, professional and technological context.